Gender identity and female labour supply in Brazil - Karen Codazzi; Valéria Lúcia Pero; André Sant'Anna (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Over the last half-century, the role of women in society has changed substantially. However, the gender income gap and the difference in labour force participation persist. Akerlof and Kranton introduce the concept of identity from sociology and social psychology at the economic analysis; based on this we search less traditional factors for understanding this persistence. We extend the analysis proposed by Bertrand et al. for Brazil. Specifically, we analyse the impact of gender identity, focusing on the prescription that 'a man should earn more than his wife' on social and economic results. Based on the Censuses for 1991, 2000, and 2010 we observed that for only 7 per cent of married couples does the wife earn more than her husband. We found evidence that the wives with greater probability of earning more than their husbands are less likely to participate in the labour force. Once she does participate in the labour force, she has a higher probability of earning less than her potential income, working fewer hours, and having an informal job.
Keywords: J12; J16; J22; 330; female labour force; gender gap; identity; labour market